Environmental Restoration of Metals-Contaminated Soils - Iskandar, I.K (CRC Press, 2009)
Written by a multidisciplinary group of scientists from around the globe Environmental Restoration of Metals-Contaminated Soils provides a summary of the current environmental remediation technology. Topics include: o Physical-Chemical processes for in situ remediation by adding amendments for stabilization o The mechanics of metal retention and release from soils o Chemical remediation method for soil contaminated with CD and Pb o The effect of soil pH on the distribution of metals among soil fractions o Physical and electrical separation methods for soil remediation o Relationship between the phytoavailability and the extractability of heavy metals o An overview on environmental restoration of Se-contaminated soils o Trace elements in the soil-plant system under tropical environment o The process of metal removal by chelation using amino acids o The effects of natural zeolelite and bentonite on the phytoavailability of heavy metals o Metal uptake by agricultural crops from sewage-sludge treated soils In many cases an integrated approach to the remediation of metals contaminated soil yields the best results. Environmental Restoration of Metals-Contaminated Soils explores the emerging issues of the biogeochemistry of trace elements in the environment and provides an approach combining elements from biology, geochemistry, hydrology, and soil physics and chemistry.